Understanding Brand Management - Ganassali, Justyna, ....- (Warszawa - Warchau : Wydawnictwo PLACET, 2023)
All partners contributed to te project final outcomes which, in addition to this book, included: an e-book containing teaching materials, assessment tools, requirements, policies and procedures as well as other recource materials, manual (for the teachers and for the students) containing all the guidelines and procedures underlying a game as an online teaching instrument and an IT platform serving as a tool for planning, impementing, and assessing the entire learning and training process along with its outcomes. The beneficiaries of the project are students whose knowledge and skills acquired during marketing and management courses will increase their attractiveness on the labor market. On the other hand, academic teachers will be able to implement ready-made, modern solutions in their courses related to brand management. Finally, all companies and institutions interested in hiring experts in international brand management.
The book is the result of an international project financed bij the Erasmus Plus Strategic Partnership Program called "Experiental education. Interactive/Intensive course of European brand Management- brandy". The main goal of this project was to design, implement and test an innovative instruments for experiental learning. These tools will be used to educate students in the field of marketing and management in order to increase their attractiveness on the labor market. The project was an opportunity to establish interdisciplinary cooperation with international experts in fields such as marketing, international brand management, new technologies and gamification. Experts represented 10 partners from all over Europe, including: University of Economics in Katowice (Poland), as the project leader, Howest University of Applied Sciences (Belgium), Université Savoie Mont Blanc (France), Bauhaus-Universität Weimar (Germany), Budapest Business School (Hungary), University of Trento (Italy), University of Bucharest (Romania), CEU Universidad Cardenal Herrera (Spain), Universidad of Leon (Spain) and HEG Geneva (Switzerland).
This publication has been funded with support from the European Commission under the Erasmus+ Programme
Keywords: Brand Management